REPRESENTASI KISAH SINGA BARONG DAN KELANA PADA IKLAN PRODUK MARJAN TAHUN 2021 - Moh Adi Rahmatullah; Jesica Zahra Safira; Renzi Prihantari; Taufikurrohman (Universitas 17 Agustus 1945 Surabaya, 2026)
This study discusses the representation of local culture in the 2021 Marjan commercial, which features the characters Singo Barong and Kelana Sewandana as symbols of the Reog Ponorogo traditional art. The purpose of this study is to identify the symbolic meanings and cultural values represented through visual elements, narration, music, and character gestures in the advertisement. This research uses a qualitative descriptive method with a content analysis approach to understand how visual and narrative elements construct cultural messages in mass media. The findings show that the 2021 Marjan advertisement presents a theme of cultural preservation through a symbolic depiction of the conflict between Singo Barong and Kelana, representing life dynamics, courage, honor, and harmony. The use of cultural elements such as masks, traditional costumes, batik motifs, and symbolic colors strengthens the image of East Javanese culture in a modern context. In addition, this advertisement plays an important role in building brand awareness through a promotional strategy that integrates cultural values with emotional storytelling, creating a connection between the audience and the product. By featuring the Reog Ponorogo characters in a modern cinematic context, this advertisement functions as a medium for both cultural preservation and transformation. Keywords: Advertisement, Cultural Representation, Reog Ponorogo, Marjan, Brand Awareness.